Sistem Informasi Pengelolaan Barang Pakai Habis di Kecamatan Bandung Kulon - Devina Aulia; Herna Febriyanti; Rini Suwartika Kusumadiarti; Neneng Yuniarty (Lembaga Penelitian dan Pengabdian pada Masyarakat (LPPM) STMIK Global Informatika MDP, 2022)
Consumables are goods that can only use once as the quantity will decrease. These goods will continue to be produced to meet office needs and daily official activities. It is necessary to regularly manage inventory items to obtain valid data and monitor the process of managing goods, especially at the Bandung Kulon District Office. The Bandung Kulon District Office does not use an application/website to manage inventory so that it makes the inventory process takes longer. In additioan, it is riskier in losing data and inefficient of recording stock using goods cards. It also affects PPTK in preparing the reports that will be submitted to BPKA at the end of each semester with a copy from the inspectorate. Therefore, The Information System Design of Consumables Goods Management in Bandung Kulon District is needed. This system was created by the waterfall method and UML (Unified Modeling Language) and for the implementation using PHP and MySql with BlackBox testing. Data collection is through direct observation and interviews with the concerned people and literature studies for references to create an efficient and precise system. Hopefully, the system can make it easier for officers to manage stock and reduce the risk of data loss as well as speed up report generation.